Transcatheter Aortic Valve Implantation: Where are we in 2020? - Sarmento-Leite,Rogerio (2020)
Abstract Aortic stenosis is an insidious disease of rapid progression after the onset of symptoms. Aortic valve replacement surgery is a well-established therapy that reduces symptoms and increases survival rates. However, the procedure may be associated with high operative mortality rates and promote comorbidity. Depending on the local reality, the prevalence of patients considered inoperable (due to medical comorbidities and age) may achieve 30%. For these patients, transcatheter aortic valve implantation (TAVI) was initially indicated; over time, the method has advanced technologically and been simplified, and become an alternative therapy for patients at low and intermediate surgical risk also, and considered one of the major advances of modern medicine.